Aces wild : a heist - DeWitt, Amanda (Peachtree Teen, 2022)
"Some people join chess club, some people play football. Jack Shannon runs a secret blackjack ring in his private school's basement. What else is the son of a Las Vegas casino mogul supposed to do? Everything starts falling apart when Jack's mom is arrested for their family's ties to organized crime. His sister Beth thinks this is the Shannon family's chance to finally go straight, but Jack knows that something's not right. His mom was sold out, and he knows by whom: Peter Carlevaro: rival casino owner and jilted lover. Gross. Jack hatches a plan to find out what Carlevaro's holding over his mom's head, but he can't do it alone. He recruits his closest friends--the asexual support group he met through fandom forums. Now all he has to do is infiltrate a high-stakes gambling club and dodge dark family secrets, while hopelessly navigating what it means to be in love while asexual. Easy, right?"--